Identification of Kv4.2 protein complex and modifications by tandem affinity purification-mass spectrometry in primary neurons - Hu, Jia-Hua; Liu, Ying; Hoffman, Dax A. (Frontiers in Cellular Neuroscience, 2022)
Proteins usually form complexes to fulfil variable physiological functions. In neurons, communication relies on synapses where receptors, channels, and anchoring proteins form complexes to precisely control signal transduction, synaptic integration, and action potential firing. Although there are many published protocols to isolate protein complexes in cell lines, isolation in neurons has not been well established. Here we introduce a method that combines lentiviral protein expression with tandem affinity purification followed by mass-spectrometry (TAP-MS) to identify protein complexes in neurons. This protocol can also be used to identify post-translational modifications of synaptic proteins. We used the A-type voltage-gated K+ channel subunit Kv4.2 as the target protein. Kv4.2 is highly expressed in the hippocampus where it contributes to learning and memory through its regulation of neuronal excitability, and synaptic plasticity. We tagged Kv4.2 with the calmodulin-binding-peptide (CBP) and streptavidin-binding-peptide (SBP) at its C-terminus and expressed it in neurons via lentivirus. Kv4.2 was purified by two-step TAP and samples were analyzed by MS. MS identified two prominently known Kv4.2 interacting proteins (dipeptidyl peptidase like [DPPs] and Kv channel-interacting proteins [KChIPs]) in addition to novel synaptic proteins including glutamate receptors, a calcium channel, and anchoring proteins. Co-immunoprecipitation and colocalization experiments validated the association of Kv4.2 with glutamate receptors. In addition to protein complex identification, we used TAP-MS to identify Kv4.2 phosphorylation sites. Several known and unknown phosphorylation sites were identified. These findings provide a novel path to identify protein-protein interactions and post-translational modifications in neurons and shed light on mechanisms of neuronal signaling potentially involved in the pathology of neurological diseases.